Pengaruh Kualitas Pelayanan dan Kepercayaan Pelanggan terhadap Keputusan Pembelian Paxel Surabaya - Moch Arif Rahman; Handy Aribowo (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Today's millennial society makes a lot of use of the internet, which is a component of the digitization process. By using a marketing strategy approach, companies are prepared to face this competition by improving the quality of their services while consumers make choices, such as choosing one of the existing delivery services. In this study using Paxel delivery services that can provide frozen food delivery services and provide opportunities for customers who have frozen food businesses. With Paxel same-day delivery, frozen food can safely carry out the delivery process inside and outside the city because of special handling complete with refrigeration facilities. The sample in this study is some Paxel Surabaya customers using a sampling technique classified as non-probability sampling with purposive sampling or sampling. From the results of these calculations , then the number of samples in this study was 96.04 rounded up to 100 respondents, namely Paxel customers in the city of Surabaya. Based on the results of the answers from the respondents tested, the result that gets the highest score lies in the Customer Trust variable which gets an average value of 3.71, which is the highest value of the other variables. This value is based on the variable category. Based on the results of the study, the purchase decision Paxel shipping services are in the high category, therefore Paxel companies are advised to maintain the quality of the services they offer. So that the trust in Paxel customers who are in the city of Surabaya can be tighter and purchasing decisions can be increased.